PEMENUHAN HAK DAN KESEJAHTERAAN ANAK YANG DIPEKERJAKAN DI KLUB MALAM NAGOYA, KOTA BATAM: Fulfilling The Rights And Welfare Of Children Employed At Nagoya Night Club, Batam City - Natalia Wulandari Hutagaol; Wahyuni Retno Wulandari (Faculty of Law, Universitas Trisakti, 2025)
This research discusses the fulfillment of the rights and welfare of children who work in Nagoya nightclubs, Batam City, based on Law Number 4 of 1979 concerning Child Welfare. Article 1 paragraph 1a of the Law emphasizes that children's welfare includes spiritual, physical and social aspects, while Article 1 paragraph 12 of Law Number 35 of 2014 emphasizes children's rights as part of human rights which must be guaranteed by the county. This research is descriptive in nature with a socio-legal approach and uses primary data from interviews. The research results and the conclusion show that economic and environmental factors cause children to work, while parents do not carry out their responsibilities. Apart from that, the government is considered to be paying little attention to the working conditions of children in the area, and Batam City Regional Regulation Number 5 of 2013 has not been implemented effectively in overcoming this problem.